The Hope Therapy Effect Toward Depression, Anxiety, and Stress of Tuberculosis Patients with Multi-Drug Resistance at Jayapura’s Healthcare Center, Papua - Sulistiyani; Lamria Situmeang; Mei Rianita Sinaga; Lalu Guntur Payasan (Journal Of Nursing Practice, 2024)
Background: Indonesia is the third country with a high-rate case of tuberculosis with multi-drug resistance, for a percentage of 5% per 100.000 population. In Papua, TB-MDR becomes the main problem of health with a successful percentage of medication at 68.7%, an indicator of WHO higher than 85%. The complexity and the prolonged occurrence make the patients to have mental health illnesses, such as depression, anxiety, and stress. The field data of depression cases consisted of 65 patients. 50% with had mild depression, 20% with moderate, and 25.55 with severe. Patients with anxiety ranged from 16.7% to 37.29%. Patients with severe stress consisted of 20%. The mental illness health problems for TB-MDR patients required the roles of the nurses, such as counseling based on HOPE therapy. Purpose: Analyzed the effects of HOPE therapy to manage depression, anxiety, and stress levels. Methods: Quasi-experimental research applied a systematically assigned control group. The population consisted of patients with TB-MDR receiving medication at Jayapura's healthcare center, 40 individuals. Results: HOPE therapy effects for depression, stress, and anxiety levels applied the Wilcoxon test. The obtained result was a p-value lower than 0.05. The results indicated the effect of HOPE therapy medication on depression, stress, and anxiety levels. The intervention group had decreased depression, stress, and anxiety levels with p-values of 0.043 and 0.012. The results contradicted the control group. The obtained p-value was higher than 0.05, indicating no effect. The p-values were 0.721, 0.532, and 0.670. Conclusion: HOPE therapy was useful for TB-MDR patients with mental illness. The administered HOPE therapy for patients could improve their confidence and hopes to live better and recover.